COUNTERACTING FINANCIAL EXCLUSION AS AN ETHICAL ASPECT OF THE ACTIVITIES OF COOPERATIVE BANKS BASED ON OWN RESEARCH - Nowacka, Anna (Acta Scientiarum Polonorum. Oeconomia, 2018)
The main purpose of this thesis is to present the opinions of clients on the ethical aspects of the activities of cooperative banks in the context of limiting financial exclusion. The author attempts to answer the questions: were clients refused with banking services, what were the reasons for this refusal, do cooperative banks offer electronic banking services to limit financial exclusion. The empirical basis of the issues discussed herein is the study of the subject literature and the results of a survey conducted among 132 clients of selected cooperative banks. The thesis assumes that financially excluded clients are those who have limited access to the products and services offered by cooperative banks. The following methods were used to develop the test results: structural and χ2 test. Based on the results of the survey, general conclusions were drawn. A small percentage of clients of the selected cooperative banks encountered difficulties in accessing banking services. Financially excluded clients are usually single men, living in the countryside, farm workers or physical workers. Electronic banking services are not very popular among clients of cooperative banks. It is difficult to identify the effect of non-cash trading on the level of financial exclusion of these institutions.